Microwave wide band absorption by carbon from Corn cob-1 - Sharon, Maheshwar; Vishwakarma, Ritesh; Phatak, Abhijeet Rajendra; Kalita, Golap; Sharma, Nallin; Sharon, Madhuri (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Corn cob, an agricultural waste, is paralyzed at different temperatures (700oC, 800oC and 900oC). Microwave absorption of carbon in the frequency range of 2 GHz to 8 GHz is reported. Carbon activated with 5% nickel nitrate showed more than 90% absorption of microwave in the frequency range from 6 GHz to 8 GHz, while carbon activated with 10% Nickel nitrate treated corn cob showed 90% absorption in the frequency range of 2.5 GHz to 5 GHz. Carbon showing the best absorption are characterized by XRD, Raman spectra and SEM . It is suggested that corn cob treatment alone with KOH did not improve the microwave absorption, whereas treatment along with nickel nitrate improved the absorption property much better. It is proposed that treatment with nickel nitrate helps in creating suitable pores in carbon which improved the absorption behavior because while treating carbon with 1N HCl helps to leach out nickel creating equivalent amount of pores in the carbon.